Vasa Previa: Diagnosis and Management. Issue 2 (June 2017) - Swank, M.L.; Garite, T.J.; Maurel, K.; Das, A.; Perlow, J.H.; Combs, C.A.; Fishman, S.; Vanderhoeven, J.; Nageotte, M.; Bush, M.; Lewis, D.
Abstract : ( Am J Obstet Gynecol . 2016;215(2):223.e1–223.e6) Data from ultrasound scans and hospital records were examined for patients who gave birth from years 2000 to 2012. Patients with a diagnosis of vasa previa or a suspected vasa previa were considered for inclusion in the study. Only patients in whom the operative, delivery and/or pathology report specifically described a vasa previa met the criteria for a confirmed diagnosis. Among 68 pregnancies, 49 of them were confirmed to have vasa previa, either based on the operative report or the pathology report or both; 47 cases (96%) were diagnosed by antenatal ultrasound scanning, and 2 cases (4%) were documented at delivery. It was found that 86% of the cases had an identifiable placental and/or maternal risk factor. Women who were confirmed to have vasa previa delivered at a mean gestational age of 34.7 weeks. A total of 8 patients needed emergent cesarean delivery at a mean gestational age of 34.6 weeks, while the remaining 41 cases underwent planned cesarean delivery at a mean gestational age of 34.7 weeks. About 20% of the neonates (n=10) were found to have respiratory distress syndrome. However, there was no report of neonatal death or other major neonatal complications.